Provider perspectives on empirical antibiotic treatment for tuberculosis-like symptoms in South Africa's private general practice sector: A qualitative study in two cities. - Jeremiah Chikovore; Jody Boffa; Sizulu Moyo; Angela Mak; Zimasa Gavu; Angela Salomon; Madhukar Pai; Amrita Daftary (PLOS Global Public Health, 2025)
While tuberculosis (TB) in South Africa is commonly treated in the public sector, some clients first seek care in the private sector. Research has demonstrated that private general practitioners (GPs) perform less well than do public sector care providers in TB testing and drug-dispensing practices. We aimed to describe GPs' decision-making practices related to empiric antibiotic treatment when presented with symptoms that may be related to TB, to inform potential interventions. Within a larger study on private sector TB management, we qualitatively interviewed 30 purposively selected GPs, who varied by gender, age, practice community, and how they managed TB and HIV in the parent study. Data were analysed through coding and constant comparison. GPs acknowledged the common use of broad-spectrum antibiotics for respiratory symptoms, driven by experience treating presumed bacterial infections and by a desire to rule out other causes before referring clients for potentially inconvenient TB tests in the private or public sector. Management decisions were susceptible to perceived or expressed pressure from clients, who may expect on-the-spot treatment. Additionally, GPs indicated using antibiotics to mitigate financial strain on economically vulnerable clients. Empirical antibiotic treatment for presentations that may be related to TB in the private sector, which can delay TB diagnosis, could be explained by the absence of accessible and affordable TB and general bacteriologic tests at the point of care, leading GPs to, among others, seek to 'rule out' possible bacterial infection. Potential interventions include increasing the salience of inappropriate antibiotic use, heightening GPs' suspicion index for TB, and linking GPs directly to public sector TB tests for clients.